Multi-specific effects of increasing T90 mesh size and amount in an Australian fish trawl - Broadhurst, Matt K.; Knuckey, Ian A.; Millar, Russell B. (Frontiers in Marine Science, 2023)
Increases in the size and amount of meshes turned 90° ('T90') in an Australian fish-trawl codend were investigated to improve the size selection of deepwater flathead Neoplatycephalus conatus and reduce discards. The conventional codend comprised 94-mm mesh throughout with normal orientation (diamond-shaped) in the posterior half but T90 in the anterior half ('half 94-mm T90' codend). Two new codends had 105-mm T90 mesh in the anterior section only ('half 105-mm T90') and throughout ('full 105-mm T90'). Both larger-meshed codends caught fewer immature deepwater flathead, but also lost some larger fish, especially the full 105-mm T90 codend, which had 80% more T90 meshes. The larger-meshed codends also allowed some discarded species to escape, but similarly affected other targets. Collected deepwater flathead morphological data support a T90 mesh size of 100 mm in the anterior codend or 94 mm throughout to maintain target sizes. However, irrespective of changes to codend meshes, owing to comparable inter-specific sizes and shapes, the discard percentage in this fishery will probably remain consistent at >75%, which is more than double the global average for fish trawls. Future efforts to improve selection in the fishery should consider modifications other than codend changes.